Pelaksanaan Seleksi Terbuka Dalam Pengisian Jabatan Pimpinan Tinggi Pratama Di Provinsi Sulawesi Barat - Syamsul Bahri; Fatmawati Fatmawati; Anwar Parewangi (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2025)
This study aims to examine and analyze the implementation of open selection and to identify the factors that influence and constrain the filling of Primary High Leadership Positions in West Sulawesi Province. The research employs a qualitative descriptive method with a case study approach. Data were collected through observation, in-depth interviews, and documentation review.Data analysis is based on the theoretical framework proposed by Hugo Horta, which encompasses seven aspects: open recruitment policy, specificity, merit system in candidate selection, communication, challenges, transparency of selection procedures, and the role of the selection committee. The data were analyzed using the Miles and Huberman model, supported by NVivo 12 Plus software to systematically visualize and manage qualitative data.The findings indicate that the implementation of open selection by the Government of West Sulawesi Province has not been optimal. Several issues were identified, including the issuance of special invitations to certain candidates, non-transparent access to implementation costs, an assessment system that lacks transparency and tends to be subjective, and the dominance of spoil system practices. Information regarding both the process and results of the selection is only accessible to limited groups and has not been widely made available to the public.